Elimination Of Escherichia Coli O157: H7 Isolated From Beef In Slaughterhouse And Traditional Markets - wirathi, Ni Wayan Purni; Kawuri, Retno; Darmayasa, Ida Bagus (Metamorfosa: Journal of Biological Sciences, 2020)
This research was conducted to determine the quality of beef in slaughterhouses and Traditional markets in Denpasar, Badung, and Klungkung, in terms of Escherichia coli and isolation E. coli O157:H7 which are suspected of contaminating beef. Experimental research was conducted in a laboratory with a heating test of E. coli O157: H7 to determine the heat resistance of E. coli O157: H7. Beef taken at Nyanggelan, Panjer market shows the highest value of E. coli which is 222.3 colonies/g, and the lowest value of E. coli is obtained in beef taken at Kaliunda abattoir which is 2.3 colonies/g. The identification results on 39 beef samples showed that all beef samples contained E. coli , 24 samples positive of E. coli O157, and 9 other samples showed positive E. coli O157:H7. The heating treatment at 60? still grows E. coli O157:H7 colonies in the Petri dish, but there has been a decrease in the number of initial colonies before the heating process. All locations were 100% contaminated with E. coli , 61.5% positive E. coli O157, and 25.6% positive E. coli O157:H7. Heating 65? for 15 seconds and 70? for 5 seconds can kill E. coli O157: H7 in beef.  Keywords: E. coli O157: H7, beef, slaughterhouses, traditional markets, heating process.